Titanium alloy surface low-temperature diffusion coating integrated composite hardening insulation treatment method
By performing the integrated composite hardening insulation treatment of low-temperature plating in the integrated composite treatment equipment of seepage plating, the problems of low hardness and poor wear resistance of titanium alloy are solved, and the high hardness, wear resistance and corrosion resistance of the surface of titanium alloy are improved, and the service life of ship parts is extended.
Patent Information
- Application Number
- CN202411710508.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Titanium alloys are less hard, poor friction and wear resistance, and are prone to galvanic corrosion in marine environments, which affects the reliable operation of ship parts.
The integrated composite hardening insulation treatment method of low-temperature permeation plating is adopted. The high-energy pulse plasma power supply and HIPIMS power supply are used to perform kV bias sputtering, pre-injection of nitrogen or oxygen ions, high-power pulse nitriding or oxygen sputtering, and sputtering to generate the TiWN-based base layer and TiWCN base surface layer in the integrated permeation plating composite treatment equipment, forming a gradient composite film layer.
It realizes low-temperature treatment of titanium alloy surface, avoids deformation, improves hardness and wear resistance, enhances insulation and corrosion resistance, and extends the service life of titanium alloy components for marine use.
Smart Images

Figure CN119710574A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface coatings, and in particular to a titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method. Background Art
[0002] Titanium alloys are widely used in the fields of shipbuilding, ocean, aerospace, process industry equipment, etc. due to their excellent properties such as low density, high specific strength, and excellent corrosion resistance. However, titanium alloys have low hardness and poor friction and wear resistance, which leads to problems such as wear, adhesion and bite. For example, the wear caused by the contact between the valve stem and the valve disc of marine titanium alloy valves has greatly affected the reliable operation of ship parts. In addition, the formation of a natural oxide layer on the surface of titanium alloys causes titanium alloys to have a higher electric potential. In the marine environment, especially when dissimilar metal related parts are assembled and contacted, the large potential difference leads to galvanic corrosion, which further aggravates the wear and is a prominent problem that plagues the long-term safe operation of ships.
[0003] In view of the wear of titanium alloys and the galvanic corrosion caused by contact with dissimilar metal parts, the existing technology mainly improves the problem by hardening and insulating the metal surface to reduce the potential difference. The main technical approaches include micro-arc oxidation, anodizing, plasma spraying, ion nitriding, physical vapor deposition, etc. Although these surface treatment technologies can improve the surface hardness of titanium alloys and improve wear resistance to a certain extent, the high temperature of the traditional nitriding process causes deformation and increase of roughness of the workpiece. The subsequent processing leads to low processing efficiency and cannot be efficiently connected with the coating process. The improvement of the hardness of titanium alloys is also limited. In addition, the corrosion resistance of the nitriding layer is poor and cannot meet the service requirements in the marine environment. Micro-arc oxidation and anodizing coatings have high porosity and low hardness. Physical vapor deposition hard coatings can achieve a significant increase in hardness, but the hardness match between the soft titanium alloy substrate and the high hardness coating is poor, and the hard layer is easily damaged and falls off under large loads.
[0004] The invention patent application with application number CN2021105831529 proposes a surface nitriding treatment method for titanium alloy parts, which is to obtain the surface to be nitrided by rough machining of the raw materials of the preheated titanium alloy parts, and the rough machining also includes machining the surface to be nitrided to the final size of the finished parts, and then performing surface nitriding treatment to reduce the impact of high-temperature deformation on the final size of the workpiece. After nitriding, the surface hardness of the workpiece can reach 1000HV, which can effectively improve the wear resistance of the titanium alloy workpiece. However, on the one hand, this technology has limited improvement on the hardness of titanium alloys, and on the other hand, the influence of deformation on the size of the workpiece is reduced by machining methods, and the nitriding temperature is not actually reduced to avoid deformation.
[0005] The invention patent application with application number CN2019109426430 proposes a method for nitriding the surface of TC4 titanium alloy using a hot wire enhanced glow discharge low-temperature plasma method. This method can achieve nitriding of the titanium alloy surface at about 500°C, forming a uniform nitrogen-containing titanium alloy solid solution phase, and significantly improving the mechanical properties of the titanium alloy. However, this method only proposes a nitriding process and does not involve the preparation of a composite film layer, especially the preparation of an integrated gradient composite film layer deposited on the substrate surface during nitriding to improve the corrosion and wear resistance of the substrate. Summary of the invention
[0006] In view of this, the present invention aims to propose a low-temperature nitriding and plating integrated composite hardening insulation treatment method for titanium alloy surface, so as to solve the deformation problem caused by the high temperature during nitriding or oxygenation treatment, and overcome the cumbersome process caused by the traditional multi-equipment and multi-process path of first nitriding and then surface finishing and then coating.
[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method, comprising the following steps:
[0009] Step 1, pickling and etching;
[0010] Step 2, placing the pickled and dried titanium alloy sample into an integrated infiltration and plating composite treatment device, wherein the integrated infiltration and plating composite treatment device is equipped with a high-energy pulse plasma power supply and a HIPIMS power supply;
[0011] Step 3: Sputtering with a kilovolt bias to pre-implant nitrogen ions or oxygen ions;
[0012] Step 4: high power pulse ion nitriding or oxygen permeation treatment;
[0013] Step 5, sputtering to generate a TiWN-based bottom layer: turning on the titanium target and the tungsten target, the titanium target and the tungsten target are controlled by a DC cathode, and a gradient multi-element TiWN coating is prepared by adjusting the ratio of Ti and W;
[0014] Step six, sputtering to form a TiWCN base layer.
[0015] Furthermore, in step 3, the high-energy pulse plasma power supply is turned on, the bias peak is adjusted to 3000-6000V for sputtering, the gas pressure is set to 0.3-0.5Pa, and the sputtering time is 30-45min; after improving the reaction activity of the titanium alloy sample matrix, 0.1-0.3m 3 / h of nitrogen or oxygen, and adjust the temperature to 350-400°C, with a treatment time of 1-1.5h, to perform pre-injection of N or O ions.
[0016] Furthermore, in step 4, the HIPIMS power supply is turned on, the working gas is adjusted to nitrogen or oxygen, and hydrogen, the bias voltage is 8-15 kV, the vacuum degree is below 10 Pa, and the nitrogen or oxygen flow rate is 0.2-0.5 m 3 / h, hydrogen flow rate is 0.1-0.2m 3 / h, temperature is 350-480℃, treatment is 5-8h, forming nitriding layer or oxygen permeating layer.
[0017] Furthermore, the thickness of the nitriding layer or the oxygen permeating layer is 1-2 μm.
[0018] Furthermore, the step five includes two stages. In the first stage, the working gas is argon and nitrogen, and the sputtering parameters of the titanium target and the tungsten target are controlled at the same time so that the ratio of the titanium target and the tungsten target components is 1:3, the HIPIMS power supply pulse high voltage is 20-25kv, the pulse width is 20-30μs, the pulse frequency is 100-150Hz, the working gas pressure of argon is 0.2-0.4Pa, and the argon partial pressure is 0.10-0.20Pa.
[0019] Furthermore, in step five, the second stage is to again adjust the sputtering parameters of the titanium target and the tungsten target during the co-sputtering process, so that the ratio of the titanium target and the tungsten target components is gradually reduced to 1:1, and finally a 0.3-0.5 μm gradient transition TiWN-based base layer is generated by reactive sputtering.
[0020] Furthermore, in the step six, the titanium target, tungsten carbide target and graphite target are turned on at the same time, the working gases are argon and nitrogen, the substrate is applied with a pulse bias of 15-20 kV, a pulse width of 20-40 μs, a pulse frequency of 100-200 Hz, a working gas pressure of 0.4-0.8 Pa, an argon flow rate of 30-50 sccm, a nitrogen flow rate of 5-10 sccm, and the ratio of Ti and WC components is adjusted from 1:1 to 1:3-1:4, and the deposition time is 3-4.5 h.
[0021] Furthermore, in step six, a TiWCN basal layer with a thickness of 4-8 μm is generated by sputtering on the surface of the titanium alloy sample.
[0022] Compared with the prior art, the titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method described in the present invention has the following advantages:
[0023] (1) The titanium alloy sample substrate is nitrided or oxygenated for strengthening and the high-hardness insulating coating is deposited in an integrated composite treatment device for nitriding and plating, which can realize integrated and efficient processing of nitriding and plating, avoid the need for surface finishing before coating, and save time and processes.
[0024] (2) The nitriding or oxygen permeation treatment is carried out at a relatively low temperature, and almost no deformation occurs to the titanium alloy matrix.
[0025] (3) The sputtering generation of TiWN-based base layer includes two stages. On the one hand, the staged sputtering can make the deposited base layer have both high bonding strength and gradient hardness, and have a better gradient transition with the subsequent surface layer hardness, thereby increasing the coating's load-bearing capacity and shear resistance. On the other hand, without changing the target material, the coating composition and structure can be better changed in stages, and the composition and structure can be naturally transitioned. It can also serve as a growth template to induce the growth of TiWCN nano-columnar crystals in the surface layer, thereby improving the surface layer's density and insulation properties.
[0026] (3) The sample after the composite treatment of the present invention has high hardness, which can reach 22GPa, and has a good hardness gradient transition effect, which greatly improves the wear resistance. The bonding force between the nitriding layer or the oxygen permeating layer and the coating reaches 60N, and it is not easy to fall off from the substrate. The surface resistance of the sample is greater than 200 megohms, and it has good corrosion resistance in the marine environment, which can improve the service life of titanium alloy parts for ships in the marine environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0028] Figure 1 This is a schematic diagram of the integrated composite treatment of kilovolt-level pulsed plasma permeation and plating according to the present invention;
[0029] Figure 2 This is a schematic diagram of the structure of the gradient coating of the integrated composite treatment of permeation and plating of the present invention;
[0030] Figure 3 This is an appearance diagram of the TA2 titanium alloy after being treated in Example 1 of the present invention;
[0031] Figure 4 This is a characterization diagram of the cross-sectional morphology and thickness of each layer of the film layer of the integrated composite treatment of permeation and plating in Example 1 of the present invention;
[0032] Figure 5 This is a microscopic morphology characterization diagram of the surface of the TA2 titanium alloy after being treated in Example 1 of the present invention;
[0033] Figure 6 This is the appearance of the Ti80 titanium alloy after being treated in Invention Example 2;
[0034] Figure 7 This is a characterization diagram of the cross-sectional morphology and thickness of each layer of the film layer of the integrated composite treatment of permeation and plating in Example 2 of the present invention;
[0035] Figure 8 This is a characterization diagram of the surface microstructure of the Ti80 titanium alloy after being treated in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be noted that the data in the following experimental examples are obtained by the inventor through a large number of experiments. Due to space limitations, only a part of them is shown in the specification, and those of ordinary skill in the art can understand and implement the present invention under these data. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these changes or modifications also fall within the scope protected by the present application.
[0037] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0038] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0039] The present invention provides a titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method, comprising the following steps:
[0040] Step 1, pickling and etching;
[0041] Specifically, in step one, the titanium alloy sample is immersed in hydrofluoric acid, then wiped with sandpaper to interrupt the continuity of the natural oxide layer on the surface, and then cleaned with acetone and alcohol, and dried with compressed air.
[0042] Step 2, placing the pickled and dried titanium alloy sample into an integrated infiltration and plating composite treatment device, wherein the integrated infiltration and plating composite treatment device is equipped with a high-energy pulse plasma power supply and a HIPIMS power supply;
[0043] Specifically, in step 2, a high-energy pulse plasma power supply is used to control the bias peak at the kilovolt level to perform ion energy regulation, replacing the temperature regulation of traditional titanium alloy nitriding, and can achieve high-energy nitrogen or oxygen injection at a low temperature below 480°C. The high-power pulsed magnetron sputtering (HIPIMS) power supply configured at the same time is conducive to the deposition of an integrated high-density nano-columnar crystal coating by regulating parameters such as pulse voltage, air pressure, and pulse width. The present invention integrates the nitriding or oxygenation of the titanium alloy substrate and the deposition of the coating, which not only avoids the formation of an oxide layer caused by sending it to the next process after nitriding or oxygenation, and the waste of resources caused by the need for additional time and manpower and material resources for cooling and polishing, but also the sample after the composite integrated treatment has a higher hardness.
[0044] Step 3: Sputtering with a kilovolt bias to pre-implant nitrogen ions or oxygen ions;
[0045] As a preferred example of the present invention, in step 3, the high-energy pulse plasma power supply is turned on, the bias peak is adjusted to 3000-6000V for sputtering, the gas pressure is set to 0.3-0.5Pa, and the sputtering time is 30-45min; after improving the reaction activity of the titanium alloy sample matrix, 0.1-0.3m 3 / h of nitrogen or oxygen, and adjust the temperature to 350-400°C, with a treatment time of 1-1.5h, to perform pre-injection of N or O ions.
[0046] Controlling the pulse bias peak at 3000-6000V can not only bombard and remove the residual oxide film layer on the surface of the titanium alloy, but also achieve the effect of gas ion implantation, avoiding temperature accumulation caused by excessive heating, so as to realize low-temperature pre-nitriding or low-temperature pre-oxygenation of titanium alloy samples.
[0047] Step 4: high power pulse ion nitriding or oxygen permeation treatment;
[0048] As a preferred example of the present invention, in step 4, the HIPIMS power supply is turned on, the working gas is adjusted to nitrogen or oxygen, and hydrogen, the bias voltage is 8-15 kV, the vacuum degree is below 10 Pa, and the nitrogen or oxygen flow rate is 0.2-0.5 m 3 / h, hydrogen flow rate is 0.1-0.2m 3 / h, temperature is 350-480℃, treatment is 5-8h, forming nitriding layer or oxygen permeating layer.
[0049] In step 4, a 1-2 μm nitriding or oxygenating layer can be formed, which can strengthen the matrix and improve the hardness. Low-temperature nitriding or oxygenating treatment at 350-480°C can avoid deformation of the carbon alloy matrix and achieve a good hardness transition between the nitriding layer and the plating layer.
[0050] Step 5, sputtering to generate a TiWN-based bottom layer: turning on the titanium target and the tungsten target, the titanium target and the tungsten target are controlled by a DC cathode, and a gradient multi-element TiWN coating is prepared by adjusting the ratio of Ti and W;
[0051] As a preferred example of the present invention, step five includes two stages. The first stage: the working gas is argon and nitrogen, and the sputtering parameters of the titanium target and the tungsten target are controlled at the same time, so that the ratio of the titanium target and the tungsten target components is 1:3, the HIPIMS power supply pulse high voltage is 20-25kv, the pulse width is 20-30μs, the pulse frequency is 100-150Hz, the working gas pressure argon is 0.2-0.4Pa, and the argon partial pressure is 0.10-0.20Pa; the second stage: the sputtering parameters of the titanium target and the tungsten target during the co-sputtering process are adjusted again, so that the ratio of the titanium target and the tungsten target components is gradually reduced to 1:1, and finally a gradient transition TiWN-based primer layer of 0.3-0.5μm is generated by reactive sputtering. The first stage is used to enhance the bonding strength between the primer layer and the nitrided matrix or the primer layer and the permeated matrix in the initial stage of sputtering deposition. The TiWN-based primer layer generated in the second stage can improve the bonding strength with the matrix after nitriding or oxygenation, and at the same time achieve a gradient transition of hardness.
[0052] Step five includes two stages. On the one hand, sputtering in stages can make the deposited base layer have both high bonding strength and a gradient increase in hardness, and have a better gradient transition with the subsequent surface layer hardness, thereby increasing the coating's load-bearing capacity and shear resistance. On the other hand, without changing the target material, the coating composition and structure can be better changed in stages, the composition and structure can be naturally transitioned, and the surface layer TiWCN nano-columnar crystals can be induced to grow as a growth template, thereby improving the surface layer density and insulation performance.
[0053] Step six, sputtering to form a TiWCN base layer.
[0054] As a preferred example of the present invention, in step six, the titanium target, tungsten carbide target and graphite target are turned on at the same time, the working gases are argon and nitrogen, the substrate is applied with a pulse bias of 15-20 kV, a pulse width of 20-40 μs, a pulse frequency of 100-200 Hz, a working gas pressure of 0.4-0.8 Pa, an argon flow rate of 30-50 sccm, a nitrogen flow rate of 5-10 sccm, and the ratio of Ti and WC components is adjusted from 1:1 to 1:3-1:4, and the deposition time is 3-4.5 h to generate a 4-8 μm thick TiWCN basal layer on the surface of the titanium alloy sample by sputtering.
[0055] The TiWCN base layer has high hardness and good insulation. In addition to improving the hardness to improve wear resistance, it can also adjust the WC component to prepare coatings with different WC contents to achieve insulation between dissimilar metals and prevent galvanic corrosion.
[0056] Figure 1 This is a schematic diagram of the integrated composite treatment of kilovolt pulse plasma infiltration and plating according to the present invention. Figure 2As shown, the sample treated by the titanium alloy surface low-temperature infiltration and plating integrated composite hardening insulation treatment method of the present invention comprises, from top to bottom: TiWCN base surface layer, TiWN base primer layer, nitriding layer or oxygen infiltration layer, and titanium alloy body base layer.
[0057] The present invention completes the nitriding or oxygen permeation strengthening of the titanium alloy sample matrix and the deposition of the high-hardness insulating coating in an integrated composite processing device for permeation and plating, which can achieve a composite integrated and efficient permeation and plating process. In the traditional process, nitriding and oxygen permeation and coating are completed in different equipment, and surface finishing is required before coating, and the improvement of the surface hardness of the titanium alloy is limited. The sample after the composite treatment of the present invention has high hardness, and the hardness can reach 22GPa. At the same time, it has a good hardness gradient transition effect, which greatly improves the wear resistance. The nitriding or oxygen permeation treatment is carried out at a relatively low temperature, and the titanium alloy matrix is almost not deformed. The bonding force between the nitriding layer or the oxygen permeation layer and the coating reaches 60N, and it is not easy to fall off from the substrate. The sample treated by the present invention has a surface resistance greater than 200 megohms, and has good corrosion resistance in the marine environment, which can improve the service life of titanium alloy parts for ships in the marine environment.
[0058] Example 1
[0059] The surface of TA2 titanium alloy was soaked and sanded with hydrofluoric acid to clean the natural oxide layer on the surface, and the roughness increased from 0.5 μm in the original state to 1.6 μm. Then, acetone, alcohol and deionized water were used for ultrasonic cleaning for 15 minutes.
[0060] The cleaned TA2 titanium alloy sample was placed in the integrated composite treatment equipment for infiltration and plating, and the high-energy pulse plasma power supply was turned on. The bias peak was adjusted at 4000V, the ion energy was adjusted for sputtering, the gas pressure was controlled at 0.4Pa, and the sputtering time was 40min. After improving the reaction activity of the titanium alloy matrix, 0.1m 3 / h of nitrogen gas and adjusted the temperature to 350-400°C for 1h to pre-inject N ions.
[0061] Turn on the HIPIMS power supply, adjust the working gas to nitrogen and hydrogen, bias voltage 8-12kV, vacuum degree below 10Pa, and nitrogen flow rate to 0.3m 3 / h, hydrogen flow rate is 0.1m 3 / h, the partial pressure of nitrogen and hydrogen is 1:8, the high-power pulse nitriding temperature is 480℃, the treatment time is 6h, and a 2μm nitriding layer is formed. The nitriding layer can strengthen the titanium alloy matrix and improve the hardness.
[0062] The titanium target and tungsten target are turned on, controlled by the DC cathode, and the ratio of Ti and W is adjusted in stages. The first stage: the working gas is argon and nitrogen, the HIPIMS power supply pulse high voltage is 20kv, the pulse width is 20μs, the pulse frequency is 150Hz, the working gas pressure is 0.3Pa of argon, the nitrogen partial pressure is 0.15Pa, and the ratio of Ti to W is 1:3. The second stage: then gradually reduce the ratio of Ti to W components to 1:1, and finally generate a 0.3μm gradient transition TiWN-based base layer through reactive sputtering. The TiWN-based base layer can not only improve the bonding strength with the substrate after nitriding, but also achieve a gradient transition of hardness.
[0063] Titanium target, tungsten carbide target and graphite target were sputtered simultaneously, and a pulse bias of 15 kV was applied to the substrate. The pulse width was 20-40 μs, the pulse frequency was 200 Hz, the working gas pressure was 0.8 Pa, the argon flow rate was 30 sccm, the nitrogen flow rate was 5 sccm, and the ratio of Ti and WC components was gradually increased from 1:1 to 1:4. The deposition time was 4 h, and a 6-8 μm thick TiWCN basal layer was sputtered on the surface of the titanium alloy sample.
[0064] Example 2
[0065] The surface of Ti80 titanium alloy was immersed in hydrofluoric acid and polished with sandpaper to clean the natural oxide layer on the surface, and the roughness increased from 0.5μm in the original state to 1.2μm. Then, acetone, alcohol and deionized water were used for ultrasonic cleaning for 15 minutes.
[0066] The cleaned Ti80 titanium alloy sample was placed in the integrated composite treatment equipment for infiltration and plating, and the high-energy pulse plasma power supply was turned on. The bias peak was adjusted at 6000V, the ion energy was adjusted for sputtering, the gas pressure was controlled at 0.3Pa, and the sputtering time was 30min. After improving the reaction activity of the titanium alloy matrix, 0.3m 3 / h of nitrogen gas and adjusted the temperature to 350-400°C for 1.5h to perform pre-injection of N ions.
[0067] Turn on the HIPIMS power supply, adjust the working gas to nitrogen and hydrogen, bias voltage to 10-15kV, vacuum degree below 0.1Pa, and nitrogen flow rate to 0.5m 3 / h, hydrogen flow rate is 0.2m 3 / h, the partial pressure of nitrogen and hydrogen is 1:6, the high-power pulse nitriding temperature is 450℃, the treatment time is 5h, and a 1μm nitriding layer is formed. The nitriding layer can strengthen the titanium alloy matrix and improve the hardness.
[0068] The titanium target and tungsten target are turned on, controlled by the DC cathode, and the ratio of Ti and W is adjusted in stages. The first stage: the working gas is argon and nitrogen, the HIPIMS power supply pulse high voltage is 25kv, the pulse width is 30μs, the pulse frequency is 100Hz, the working gas pressure is 0.35Pa of argon, the nitrogen partial pressure is 0.20Pa, and the ratio of Ti to W is 1:3. The second stage: then gradually reduce the ratio of Ti to W components to 1:1, and finally generate a 0.5μm gradient transition TiWN-based base layer through reactive sputtering. The TiWN-based base layer can not only improve the bonding strength with the substrate after nitriding, but also achieve a gradient transition of hardness.
[0069] Titanium target, tungsten carbide target and graphite target were sputtered simultaneously, and a pulse bias of 20 kV was applied to the substrate. The pulse width was 20-40 μs, the pulse frequency was 200 Hz, the working gas pressure was 0.4 Pa, the argon flow rate was 50 sccm, the nitrogen flow rate was 10 sccm, and the ratio of Ti and WC components was gradually increased from 1:1 to 1:3. The deposition time was 4.5 h, and a 4-6 μm thick TiWCN basal layer was sputtered on the surface of the titanium alloy sample.
[0070] Figure 3-5 They are respectively the appearance picture of TA2 titanium alloy treated by the method of Example 1, the cross-sectional morphology of the film layer treated by the integrated infiltration and plating composite treatment and the characterization picture of the thickness of each layer, and the characterization picture of the surface microscopic morphology. Figure 6-8 They are respectively the appearance of the Ti80 titanium alloy treated by the method of Example 2, the cross-sectional morphology of the film layer treated by the integrated composite treatment of infiltration and plating and the thickness of each layer, and the surface microscopic morphology. It can be seen that the treatment method of the present invention can obtain a titanium alloy with good appearance, smoothness, and no deformation, and the TiWCN base surface layer can be well deposited on the TiWN base layer, thereby improving the hardness and insulation strength.
[0071] The hardness and bonding strength of the samples of Example 1 and Example 2 are shown in Table 1. The test instrument used for nanohardness is a nanoindentation tester, and the test instrument used for bonding strength is a nanoscratch tester. Five groups of samples were taken for testing in each example.
[0072] Table 1
[0073]
[0074] As can be seen from Table 1, the samples of Example 1 and Example 2 obtained by the treatment method of the present invention have a nanohardness of 20.24-21.56 GPa and a bonding force of 59.4-60 N, which can greatly improve the hardness and friction and wear resistance. The deposited TiWCN base layer has a strong bonding force, which can prevent galvanic corrosion and severe wear that occur when the titanium alloy serving in the marine environment contacts with dissimilar metal parts.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A titanium alloy surface low-temperature permeation integrated composite hardening insulation treatment method, characterized in that: The steps include: Step 1, pickling and etching; Step 2, placing the pickled and dried titanium alloy sample into an integrated infiltration and plating composite treatment device, wherein the integrated infiltration and plating composite treatment device is equipped with a high-energy pulse plasma power supply and a HIPIMS power supply; Step 3: Sputtering with a kilovolt bias to pre-implant nitrogen ions or oxygen ions; Step 4: high power pulse ion nitriding or oxygen permeation treatment; Step 5, sputtering to generate a TiWN-based bottom layer: turning on the titanium target and the tungsten target, the titanium target and the tungsten target are controlled by a DC cathode, and a gradient multi-element TiWN coating is prepared by adjusting the ratio of Ti and W; Step six, sputtering to form a TiWCN base layer.
2. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 1 is characterized in that: In the step 3, the high-energy pulse plasma power supply is turned on, the bias peak is adjusted to 3000-6000V for sputtering, the gas pressure is set to 0.3-0.5Pa, and the sputtering time is 30-45min; after improving the reaction activity of the titanium alloy sample matrix, 0.1-0.3m 3 / h of nitrogen or oxygen, and adjust the temperature to 350-400°C, with a treatment time of 1-1.5h, to perform pre-injection of N or O ions.
3. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 1, characterized in that: In step 4, the HIPIMS power supply is turned on, the working gas is adjusted to nitrogen or oxygen, and hydrogen, the bias voltage is 8-15 kV, the vacuum degree is below 10 Pa, and the nitrogen or oxygen flow rate is 0.2-0.5 m 3 / h, hydrogen flow rate is 0.1-0.2m 3 / h, temperature is 350-480℃, treatment is 5-8h, forming nitriding layer or oxygen permeating layer.
4. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 3 is characterized in that: The thickness of the nitriding layer or the oxygen permeating layer is 1-2 μm.
5. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 1, characterized in that: The step five includes two stages. In the first stage, the working gas is argon and nitrogen, and the sputtering parameters of the titanium target and the tungsten target are controlled at the same time so that the ratio of the titanium target and the tungsten target components is 1:3, the HIPIMS power supply pulse high voltage is 20-25kv, the pulse width is 20-30μs, the pulse frequency is 100-150Hz, the working gas pressure of argon is 0.2-0.4Pa, and the argon partial pressure is 0.10-0.20Pa.
6. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 5, characterized in that: In the step five, the second stage is to adjust the sputtering parameters of the titanium target and the tungsten target during the co-sputtering process again, so that the ratio of the titanium target and the tungsten target components is gradually reduced to 1:1, and finally a gradient transition TiWN-based bottom layer of 0.3-0.5 μm is generated by reactive sputtering.
7. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 1, characterized in that: In the step six, the titanium target, tungsten carbide target and graphite target are turned on at the same time, the working gases are argon and nitrogen, the substrate is applied with a pulse bias of 15-20 kV, a pulse width of 20-40 μs, a pulse frequency of 100-200 Hz, a working gas pressure of 0.4-0.8 Pa, an argon flow rate of 30-50 sccm, a nitrogen flow rate of 5-10 sccm, and the ratio of Ti and WC components is adjusted from 1:1 to 1:3-1:4, and the deposition time is 3-4.5 h.
8. The titanium alloy surface low-temperature permeation and plating integrated composite hardening insulation treatment method according to claim 1, characterized in that: In the step six, a TiWCN basal layer with a thickness of 4-8 μm is generated by sputtering on the surface of the titanium alloy sample.
Citation Information
Patent Citations
Tie Strap With Hardened Integrated Rivet For Saw Chain
CN105757175A
Die-casting die with surface recombination-structured impact resistant coating and preparation method thereof
CN108130507A
Nitrided WC-Co-TiC-TiN hard alloy and preparation method and application thereof
CN117051300A
AlTiN-WS2 low-friction-coefficient wear-resistant coating and preparation method thereof
CN117286450A
Energy-efficient window coatings transmissible to wireless communication signals and methods of fabricating thereof
US20220221636A1
Cited By
TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment as well as treatment method and application of TC4 titanium alloy surface strengthening layer
CN121046773A